2020
DOI: 10.1002/jsfa.10929
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water deficit on growth and performance of drip irrigated sweet potato varieties

Abstract: BACKGROUND There are many scientific studies on performance of different sweet potato varieties under water deficits, however, no study on Koganesengan and Beniazuma varieties has been found in the literature. This study was aimed to investigate the effects of water deficit levels (control‐WD0, low‐WD25, medium‐WD50 and high‐WD75 water deficit levels) on growth, yield and quality parameters, water use efficiency and water‐yield response factor values of these sweet potato varieties under drip irrigation. RESUL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Price difference in lower quality products remaining constant after a drought is evidence of a more stable long‐run market price equilibrium in this market. This can be explained by the negative association between product quality and water stress in potato farming (Karakas et al., 2020; Wagg et al., 2021), which can result in a larger drop in the supply of higher quality potatoes, especially if farmers lack access to irrigation technology. No substantial differences are found in price reaction to drought between tomato quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Price difference in lower quality products remaining constant after a drought is evidence of a more stable long‐run market price equilibrium in this market. This can be explained by the negative association between product quality and water stress in potato farming (Karakas et al., 2020; Wagg et al., 2021), which can result in a larger drop in the supply of higher quality potatoes, especially if farmers lack access to irrigation technology. No substantial differences are found in price reaction to drought between tomato quality.…”
Section: Resultsmentioning
confidence: 99%
“…The growth of potato is highly responsive to water stress (Karakas et al., 2020; Wagg et al., 2021), although tomatoes are relatively more sensitive to extreme changes in temperature and humidity, which makes it more perishable than potatoes (Boiteau and Pingali, 2022). Climate change studies estimate an intensification of aridity in the north zone, advances of the desert toward the south, and less precipitation in the central zone at the end of the 21st century in Chile (FAO, 2010; Núñez and Verbist, 2018).…”
Section: Agriculture and Climate In Chilementioning
confidence: 99%
“…Gomes and Carr (2003a) measured WU from well-watered crops as 800 mm during the rains and 550 mm during the dry season, while the WU for the rain-fed crops was 360 and 180 mm, respectively. Karakas et al (2021) found that seasonal water consumption of two sweetpotato cultivars was calculated as 808 and 826 mm, under no water deficit in Turkey. Gomes and Carr (2003b) recorded WUEs of 13 kg•ha −1 •mm −1 in the rains and 24 kg•ha −1 •mm −1 in the dry season, indicating each unit of water "lost" in the dry season was nearly twice as productive as the same amount of water consumed by the crop in the rains.…”
Section: Water Management In Sweetpotato Productionmentioning
confidence: 99%
“…Most of the water research in sweetpotato has been on the effects of water deficit as most of this crop is produced in areas that are primarily rain fed, such as the drought‐prone tropics. Some cultivars have been shown to be susceptible to drought (Adebola & Abe, 2013; Karakas et al., 2021). Water deficits reduce leaf water potential and total WU, and subsequently reduce stomatal conductance, leaf area, root mass, total plant mass, and tuber yield (Sivan et al., 1996).…”
Section: Water Management In Sweetpotato Productionmentioning
confidence: 99%
See 1 more Smart Citation